Potentilla discolor ameliorates LPS-induced inflammatory responses through suppressing NF-κB and AP-1 pathways - Xiaoyu Zhang (Elsevier, 2021)
Potentilla discolor Bunge (PD) is a traditional Chinese medicine which has been widely used for the treatment of various inflammatory diseases (e.g., diarrhea, fever and furuncle). However, few studies focused on its effect on classical inflammation. This study aimed to investigate the anti-inflammatory effect and potential mechanism of the ethanol extract of the whole herbs of PD (EPD) in lipopolysaccharide (LPS)-induced inflammatory models. The obtained results showed that EPD decreased supernatant NO, tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) in LPS-activated RAW264.7 cells and mouse peritoneal macrophages. Moreover, its effect on NO was attributed to the suppression of iNOS expression rather than its activity. At the transcriptional level, EPD suppressed iNOS, TNF-α and MCP-1 mRNA expressions in LPS-stimulated RAW264.7 cells. Further study showed that EPD didn’t affect the phosphorylation and degradation of IκBα, but yet impeded the nuclear translocation of p65 to inhibit NF-κB activation. Meanwhile, it also prevented JNK, ERK1/2 and p38 phosphorylation to dampen the activation of AP-1. In endotoxemia mouse model, EPD not only decreased interleukin-6, TNF-α and MCP-1 levels in serum, but also potently ameliorated diarrhea. These findings provide the theoretical basis for PD to treat inflammatory diseases, especially intestinal inflammation.